The Influence of Product Quality, Price Perception, and Service Quality on Customer Satisfaction at Pondok Poteng Restaurant, Singkawang - Mia Sara; Muhammad Ebuziyya Alif Ramadhan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of product quality, price perception, and service quality on customer satisfaction at Pondok Poteng Restaurant in Singkawang City. This research uses an associative quantitative approach with a total of 100 respondents selected through purposive sampling. Data were collected through questionnaires and interviews. The results of multiple linear regression analysis show the equation Y = 1.018 + 0.219X₁ + 0.238X₂ + 0.223X₃ with a correlation coefficient (R) of 0.712, indicating a strong relationship. The coefficient of determination (R²) is 50.6%, which means that 50.6% of the variation in customer satisfaction is influenced by product quality, price perception, and service quality. The F test shows an F calculated value of 32.842, which is greater than the F table value of 2.70, with a significance value of 0.000 < 0.05, meaning that the independent variables simultaneously have a positive and significant effect. The partial t test also shows that each variable product quality, price perception, and service quality have a positive and significant effect on customer satisfaction. In conclusion, these three variables have a real contribution to increasing customer satisfaction. This study recommends strengthening product quality standards, adjusting pricing strategies to be more competitive, and improving service management to maintain customer loyalty. Future research is expected to add other variables, such as promotion or brand image, so that the results can be more comprehensive.